A CRISIS MANAGEMENT MODEL FOR MARKETING EDUCATION: REFLECTIONS ON MARKETING EDUCATION SYSTEM'S TRANSFORMATION IN VIEW OF THE COVID-19 CRISIS. Issue 4 (2nd October 2021) - Spais, George; Paul, Pallab
ABSTRACT: Our primary objective is to apply a crisis management model to marketing education in distress due to the current COVID-19 pandemic. We use a strategic approach to managing crisis, first introduced by Burnett, to provide a conceptual framework for managing teaching turmoil and triumphs during this pandemic. We conduct an in-depth discussion of the literature and, adopting a critical realist's perspective, provide current examples of universities' best practices and decisions for each of the three phases of crisis management (identification, confrontation, and reconfiguration) for successful recovery during these trying times. As the gap between theory and practice remains a critical concern among scholars, we hope our article and proposed framework present a unique opportunity to explore and study how unexpected changes occur in higher education, and their remedies. Based on the need to reflect on the nature of current marketing education through crisis management, we identify the implications of our framework and offer valuable suggestions for future research.